Implementation And Development Of E-Voting System For Election Of Student Council Chairperson Of SMP Negeri 10 PEKANBARU - Yuvi Darmayunata; Febrizal Alfarasy Syam; Afriansyah Afriansyah (Journal of Applied Engineering and Technological Science (JAETS), 2020)
Intra-School Student Organization is an organization that is at the school level in Indonesia, starting with junior high schools and senior high schools. The student council is managed and managed by students who are chosen to be student council. Usually this organization has a mentor from the teacher chosen by the school. Student council members are all students who are in one school where the student council is located. In an effort to elect the student council president, the researchers created a web-based information system in selecting the student council president. E-voting is an electoral system where data is recorded, stored and processed in the form of digital information. In the election of the chairman is always a problem in carrying out his election, such as having to prepare space, paper, and others. And after that it takes time in completing the vote count, it also requires a lot of people or committees in carrying out the chairman's election, lack of transparency in vote counting, there are still errors in vote counting.